On the suitability of thermogravimetric balances for the study of biomass pyrolysis. (15th September 2020) - Barr, Meredith R.; Volpe, Maurizio; Messineo, Antonio; Volpe, Roberto
Abstract: In fixed-bed pyrolysis reactors, the stacking of sample particles often leads to higher yields of solid pyrolysis products (chars) than are obtained from other types of reactors. This phenomenon is particularly emphasised in thermogravimetric (TG) balances, which unlike many fixed-bed reactors, do not sweep gas through the stationary bed of pyrolysing sample. Gas is swept through the sample bed to reduce the residence time of tar vapours in close proximity to chars, which affects the extent to which these vapours will condense onto the surface of chars and repolymerise, thus increasing char yield. Depth of the sample bed affects this residence time, and thus affects char yield. In this work, the sensitivity of typical analyses of biomass thermogravimetry to variations in bed depth have been assessed. Results of these analyses, including product distributions, proximate compositions, and kinetic predictions, carried out on microcrystalline cellulose and birch wood hydrochar samples produced at temperatures ranging from 160 to 280 °C, have been shown to be sensitive to variations in bed depth, and it has been demonstrated that this sensitivity is amplified at higher heating rates and temperatures. Thus, when a single sample mass is used for any of these typical TG analyses, as is common in published literature, the results are not fundamental properties of the material tested but rather a product of the exact experimental design employed. Future work is needed to identify reactor and experimental design guidelines to minimise this sensitivity in fixed-bed reactors.